1998
DOI: 10.1007/s002449900295
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Metals Associated with Mining Waste in Sediments, Biofilm, Benthic Macroinvertebrates, and Fish from the Coeur d'Alene River Basin, Idaho Note: Use of trade names does not imply endorsement of a product. -->

Abstract: Arsenic, Cd, Cu, Pb, Hg, and Zn were measured in sediments, biofilm, benthic macroinvertebrates, and fish from the Coeur d'Alene (CDA) River to characterize the pathway of metals transfer between these components. Metals enter the CDA Basin via tributaries where mining activities have occurred. In general, the ranking of food-web components from the greatest to smallest concentrations of metals was as follows: biofilm (the layer of abiotic and biotic material on rock surfaces) and sediments > invertebrates > w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
99
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(111 citation statements)
references
References 29 publications
7
99
1
Order By: Relevance
“…Total metal content observed in this study compares well with the literature data (Reece et al 1978;Farag et al 1998;Paulson 2001). This site is contaminated with high levels of Zn (0.75% mass) and Pb (0.5% mass; Table 2), both of which are toxic to biota (Brim et al 1999;Konopka et al 1999;Sani et al 2001;Lin et al 2003).…”
Section: Elemental Analysissupporting
confidence: 88%
See 1 more Smart Citation
“…Total metal content observed in this study compares well with the literature data (Reece et al 1978;Farag et al 1998;Paulson 2001). This site is contaminated with high levels of Zn (0.75% mass) and Pb (0.5% mass; Table 2), both of which are toxic to biota (Brim et al 1999;Konopka et al 1999;Sani et al 2001;Lin et al 2003).…”
Section: Elemental Analysissupporting
confidence: 88%
“…Contamination of lateral lakes adjacent to the delta (Harrington et al 1998a;Sprenke et al 2000;Bostick et al 2001), CdAR and upstream tributary contamination (Maxfield et al 1974b;Reece et al 1978;Paulson 1997;Farag et al 1998Farag et al , 2000La Force et al 1998;Balistrieri et al 2003;Box et al 2005), and downstream of LCdA (Grosbois et al 2001) have also been studied. Horowitz et al (1995a) found that the CdAR and adjacent lake sediments were the most heavily contaminated.…”
Section: Introductionmentioning
confidence: 99%
“…Maximum TSMD concentrations of all three metals in crayfish were also about ten-fold lower than those in invertebrates from tailings-contaminated reaches of the Coeur d'Alene River, Idaho (Farag, Woodward, Goldstein, Brumbaugh, & Meyer, 1998, but Pb, Cd, and Zn concentrations documented by Wildhaber et al (1997Wildhaber et al ( , 2000 in crayfish and other invertebrates from SR tributaries exceeded those associated with deleterious effects in fish elsewhere (Farag, Boese, Woodward, & Bergman, 1994;Woodward, Brumbaugh, DeLonay, Little, & Smith, 1994). Metals concentrations in 2001-2002 crayfish were also variable; those with the greatest ww Pb and Zn concentrations came from Site 3u (Fig.…”
Section: Metals In Fish and Crayfishmentioning
confidence: 80%
“…Metal contamination and habitat disturbance in streams draining the Old Lead Belt are reflected in substantial biological effects, including alteration of benthic invertebrate communities ) and inhibition of Pb-sensitive enzyme systems in fish (Schmitt et al, 1993). The most severe example of Pb contamination of aquatic environments in the United States is the Coeur d_Alene River watershed of Idaho, where some stream and reservoir biota contain tissue Pb concentrations that are 10-to 100-fold greater than those in the Viburnum Trend (Farag et al, 1998; Table VI). Exposure to high levels of Pb and associated metals in the Coeur d_Alene watershed has been linked to toxic effects in waterfowl and fish (Blus, Henny, Hoffman, & Grove, 1991;Farag et al, 1999).…”
Section: Changes In Metal Exposure Over Timementioning
confidence: 99%